A socio-historical analysis of development of the ekklesia in the first Pauline Christian ́s communities. (Theological Kronos, 2019)
The purpose of this article is to present to the reader the socio-historical development of the word ekklesia in the first Christian communities led by the apostle Paul. This article shows the reader the applicability that the apostle proposes for the Christian ekklesia by referring to the idea of the Greco-Roman ekklesia and the translation of the Hebrew word qahal (קָהַל (into Greek by the Septuagint, the LXX. This is an analysis of the way in which Paul redefined this word, which at first did not have a close link with Christianity, but which provides important aspects that make the word ekklesia a symbolic identity for the socio-religious behaviors of the first Christian communities in the first century.
Keywords: Church-Ekklesia; Jews; Greco-Roman; temple; homefamily; symbol; identity